Donnie Darko and the Messianic Motif - Dodd, Kevin V. (The journal of religion and film, 2009)
Savior or deliverer movies are a staple in today’s theaters. Often they are action/adventure films where they tend to substitute action for character development. In the first background section I will use an ancient Hindu epic to demonstrate that this is by no means novel. But there have also been richer films that are psychologically, religiously, and often politically, savvy. Many have been examined in this journal, including Cool Hand Luke, One Flew Over the Cuckoo’s Nest, and the highly provocative Breaking the Waves. The last especially points to a particular category of savior film, the Messianic, modeled primarily on the Christian story of Jesus of Nazareth. Rooted in Jewish mythology, this foundational Christian myth, understood a particular way, tells of an unlikely, misunderstood, and even rather foolish savior figure, who is properly appreciated by his followers only after this community finally becomes aware of the effects of his ultimate sacrifice. I will flesh this out a little also in the first background section. I will then turn to Donnie Darko, contending that this film should stand with the best of this genre. Besides having a compelling storyline and clever subplots, it introduces novel elements in the Christ story, particularly in the scope of the messianic sacrifice and in the surprising absence of any resurrection.